Modern problems and prospects of tax on professional income application - N. G. Morozova; M. V. Tipalina (Вестник университета)
The article discusses debatable issues of taxation of self-employed citizens in the Russian Federation. The purpose of the study is to analyze the current practice of taxation of self-employed citizens, identify urgent problems that arise during implementation of the experiment on professional income tax application, and search for approaches to their solution. The statistical data of the Federal Tax Service of the Russian Federation on the number of registered tax payers and their distribution by region have been analyzed as well as of tax revenues to the respective budget, advantages and disadvantages of similar system, and legal consolidation of the status of self-employed citizens. Ideas on how to improve efficiency of the tax regime have been generated. The study concludes that the experimental taxation regime for self-employed citizens has to be developed further. The results obtained can be used in the development of decisions to improve tax on professional income at the end of the experimental period and in development of draft laws to improve provisions of the state tax policy relating to self-employed citizens.